Observation on different reducing power of cocatalysts on the Ziegler–Natta catalyst containing alkoxide species for ethylene polymerization. Issue 20 (7th May 2014) - Hongmanee, Goond; Sripothongnak, Saovalak; Jongsomjit, Bunjerd; Praserthdam, Piyasan
ABSTRACT In this work, the effects of three types of cocatalyst having different alkyl groups, such as triethylaluminium (TEA), triisobutylaluminum (TiBA), and trioctylaluminium (TnOA), and their concentrations on the catalytic activity and polymer properties were investigated for the Ziegler–Natta catalyst containing alkoxide species. The drastic escalation of catalytic activity was observed when the ratio of Al/Ti was increased only for TEA because of its good diffusivity as proven by the electron spin resonance technique. Moreover, it was found that the characteristic of the alkyl group in cocatalyst affected on the chain transfer ability. The chain transfer ability of TnOA was found to be equal to the TiBA in spite of its concentration was higher. By the way, the cocatalyst types and their concentrations did not affect on the variety of active sites as seen in molecular weight distribution of polymer. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40884.